The Effect of Antioxidants Added to Culture Medium on Blastocyst Development Rates - Mehmet Burakalp Yusuflu; Sakine Ülküm Çizmeci (Turkish Journal of Agriculture: Food Science and Technology)
The present study, it was aimed to determine the effect of antioxidants added to culture media on blastocyst development rates in in vitro embryo production. The material of the study consisted of oocytes collected from the ovaries taken from the slaughterhouse. Cumulus oocyte complexes (COC) were collected and classified under a stereomicroscope. Oocytes included in the study were subjected to maturation and fertilization stages. Probable zygotes were transferred to the culture (IVC) containing antioxidants (L-ergothionine 100 μM (n: 163), Vitamin E 100 μM (n: 151) Cysteamine 50 μM (n: 154) and were cultured in a tri gas incubator (Hera Cell- 6% O2%, 6%CO2, 88%N). Blastocyst rates and embryo quality were determined on the 6th and 7th days in culture medium. Differences in IVMFC stages were evaluated by chi-square test. 966 oocytes were collected from 162 ovaries collected from the slaughterhouse. It was determined that the number of oocytes per ovary was 5,96, and the number of A and B quality oocytes was 4.26. It was determined that 655 (94.93%) of a total of 690 oocytes undergoing in vitro maturation were mature. The cleavage rates of the groups were 83.44%; 80.79%; 79.87%, and 83.96%, respectively. 140 (21.37%) blastocysts were obtained from 655 oocytes taken into the culture stage and the blastocyst rates in the groups were 33.13%; 8.61%; 7.79%, and 32.62%, respectively. As a result of the study, it was determined that the rates of blastocysts in the L-ergothioneine added the group was similar to the control group, but the blastocyst rates decreased significantly in the cysteamine and Vitamin E added groups. It was thought that this decrease might have been affected by the dose of antioxidants or the adequacy of oocyte development